2012
DOI: 10.2478/10004-1254-63-2012-2133
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglyphid Mites as a Source of Work-Related Allergens

Abstract: Pyroglyphid mites are primarily associated with allergen exposure at home; hence the name house dust mites. However, we have found numerous studies reporting pyroglyhid mite levels in public and occupational settings. This review presents the fi ndings of house dust mite allergens (family Pyroglyphidae, species Dermatophagoides) as potential work-related risk factors and proposes occupations at risk of house dust mite-related diseases. Pyroglyphid mites or their allergens are found in various workplaces, but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It is also possible that other common aeroallergens (eg, pets, pyroglyphid mites) may have contributed to cases in the public environments as observed in previous literature. 28,29 The increased incidence of WRA among workers in the education industry also raises concern as to whether there might be a parallel risk for students who share the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that other common aeroallergens (eg, pets, pyroglyphid mites) may have contributed to cases in the public environments as observed in previous literature. 28,29 The increased incidence of WRA among workers in the education industry also raises concern as to whether there might be a parallel risk for students who share the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…are potential work-related risk factors [166]. Several studies have reported high levels of domestic mite allergens in occupational settings, particularly in schools and day care centers, but clinically relevant exposures can also been found in various workplaces, including poultry farms, hotels, cinemas, libraries, public transportation, fishing-boats, submarines, and churches [166]. …”
Section: Clinical Pictures: Asthma Rhinitis/rhinosinusitis Atopic Dmentioning
confidence: 99%
“…These authors found that inhalable dust mite allergen concentrations in most of the workplaces investigated were higher than those in living areas, and significant differences were found for textile recycling, bed feather filling, feed production, grain storage and cattle stables [167]. These studies [166, 167] show that exposure to house dust mite allergens can be higher in occupational than in domestic settings, and therefore subjects sensitized to house dust mites can experience worsening or aggravation of respiratory symptoms in the workplace, leading to work-exacerbated asthma.…”
Section: Clinical Pictures: Asthma Rhinitis/rhinosinusitis Atopic Dmentioning
confidence: 99%
“…While HDM allergen levels measured in this study in north-east Scotland indicate low risk (18), the small sample size can hardly serve to predict the distribution of HDM allergen, especially the levels that might constitute a health risk. Further investigations of HDM levels (including Der p 1 measurements) in UK households and vehicle dust are warranted, especially where high household HDM levels are likely to be found (i.e.…”
Section: Resultsmentioning
confidence: 99%